2017
DOI: 10.1186/s12933-017-0602-y
|View full text |Cite
|
Sign up to set email alerts
|

Pemafibrate (K-877), a novel selective peroxisome proliferator-activated receptor alpha modulator for management of atherogenic dyslipidaemia

Abstract: Despite best evidence-based treatment including statins, residual cardiovascular risk poses a major challenge for clinicians in the twenty first century. Atherogenic dyslipidaemia, in particular elevated triglycerides, a marker for increased triglyceride-rich lipoproteins and their remnants, is an important contributor to lipid-related residual risk, especially in insulin resistant conditions such as type 2 diabetes mellitus. Current therapeutic options include peroxisome proliferator-activated receptor alpha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 65 publications
4
98
0
1
Order By: Relevance
“…20,21 Pemafibrate, a novel selective PPARa modulator, has higher potency and subtype selectivity for PPARa than fenofibrate. 22 Phase 2 and 3 studies demonstrated that pemafibrate treatment, with or without statins, resulted in a significant decrease in fasting TG level and increase in HDL-C level and suggested that pemafibrate may have a superior risk/benefit profile to fenofibrate. [23][24][25][26][27] In vivo and in vitro studies found that pemafibrate enhanced CEC, RCT, and TRL catabolism, suppressed TRL production, and exerted anti-inflammatory and antiatherosclerotic effects.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Pemafibrate, a novel selective PPARa modulator, has higher potency and subtype selectivity for PPARa than fenofibrate. 22 Phase 2 and 3 studies demonstrated that pemafibrate treatment, with or without statins, resulted in a significant decrease in fasting TG level and increase in HDL-C level and suggested that pemafibrate may have a superior risk/benefit profile to fenofibrate. [23][24][25][26][27] In vivo and in vitro studies found that pemafibrate enhanced CEC, RCT, and TRL catabolism, suppressed TRL production, and exerted anti-inflammatory and antiatherosclerotic effects.…”
Section: Introductionmentioning
confidence: 99%
“…5a). To further explore if targeted DNA demethylation of the Fgf21 promoter affected mRNA expression responses, we examined the impact of K-877, a novel selective PPARα modulator (SPPARMα) 18 www.nature.com/scientificreports www.nature.com/scientificreports/ response. Upon K-877 administration, Fgf21 mRNA expression was significantly increased, when transiently transfected with either gRNA1, gRNA2, or gRNA1+2 relative to scramble gRNA.…”
Section: Dnmt1 and Dnmt3a Contribute To Re-methylation In The Fgf21 Pmentioning
confidence: 99%
“…It is primarily liver eliminated, whereas fenofibrate, gemfibrozil and bezafibrate have a predominant kidney elimination. 77 Phase 2 studies. The effectiveness of pemafibrate was evaluated in patients on statins (JapicCTI-121837 and JapicCTI-132067).…”
Section: Ppar-modulator -Pemafibratementioning
confidence: 99%